Diagnosis and treatment of epiploic appendagitis in a Middle Eastern country: An observational retrospective analysis of 156 cases - Ayman El‐Menyar (17746911) (2024)
Background Epiploic appendagitis (EPA) is an uncommon emergency surgical condition that causes acute abdominal pain, rendering a list of differential diagnoses. Therefore, careful examination and imaging tools are required. EPA is a self‐limiting condition that can be resolved in 1–2 weeks and rarely needs surgical intervention. Its low incidence makes EPA less well‐known among the public and some medical professionals, and it is frequently under‐diagnosed. We aimed to explore the incidence, clinical presentation, modalities of imaging to diagnose and options for treating EPA. Methods An observational retrospective analysis was conducted between 2016 and 2022 at a tertiary hospital in an Arab Middle Eastern country. Results There were 156 EPA cases diagnosed over six years, with a mean age of 33 years. Males represented 82% of the cohort. The entire cohort was treated non‐operatively except for eight patients who had surgical intervention using open or laparoscopic surgery. The diagnosis was made by a computerized tomographic scan (CT). However, plain X‐ray, abdominal ultrasound, and magnetic resonance imaging (MRI) were performed initially in a few selected cases to rule out other conditions. No specific blood test indicated EPA; however, a histopathology examination was diagnostic. No mortality was reported in the study cohort. Conclusion This is the most extensive study analyzing EPA patients from the Middle East. EPA is a rare and mostly self‐limiting acute abdominal disorder; however, early ultrasound and CT scan can pick it up quickly after a high index of suspicion. Other Information Published in: World Journal of Surgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/wjs.12161